The Efficacies of Cell‐Penetrating Peptides in Accumulating in Large Unilamellar Vesicles Depend on their Ability To Form Inverted Micelles. Issue 6 (23rd February 2014) - Swiecicki, Jean‐Marie; Bartsch, Annika; Tailhades, Julien; Di Pisa, Margherita; Heller, Benjamin; Chassaing, Gérard; Mansuy, Christelle; Burlina, Fabienne; Lavielle, Solange
Abstract In this study, the direct translocation of cell‐penetrating peptides (CPPs) into large unilamellar vesicles (LUVs) was shown to be rapid for all the most commonly used CPPs. This translocation led within a few minutes to intravesicular accumulation up to 0.5 mM, with no need for a transbilayer potential. The accumulation of CPPs inside LUVs was found to depend on CPP sequence, CPP extravesicular concentration and phospholipid (PL) composition, either in binary or ternary mixtures of PLs. More interestingly, the role of anionic phospholipid flip‐flopping in the translocation process was ascertained. CPPs enhanced the flipping of PLs, and the intravesicular CPP accumulation directly correlated with the amount of anionic PLs that had been transferred from the external to the internal leaflet of the LUV bilayer, thus demonstrating the transport of peptide/lipid complexes as inverted micelles.